Peat land management in Liang Anggang Protected Forest by Sukamaju Peat Care Society (PCS), South Kalimantan - Nor Ifansyah; Junaidah Junaidah (Jurnal GALAM, 2020)
Peatland management in protected forest area can be carried out through Social Forestry (SF) programs. Social forestry (SF) is a form of solution to the resolution of peatland management problems, both in the context of efforts to restore degraded peat as well as efforts to resolve sosial conflicts and overlapping land and management permits. The purpose of this research is to determine the patten of land management and the application of sosial forestry by Sukamaju Peat Cares Society (PSC), Landasan Ulin, South Kalimantan. The official permit to cultivate the land is contained in SK. 5902/Menlhk-PSKL/PKPS/PSL.0/9/2018 dated September 14, 2018 with scheme Community Forest (CF). Land management patterns carried out are monoculture, agroforestry, agrosilvopasture, apiculture, agrosilvofishery and revegetation. Management of peatlands is carried out independently and also involves stakeholders, including: The South Kalimantan Provincial Foresty Service, Kayu Tangi Forest Management Unit, Lambung Mangkurat University, Peat Restoration Agency, Kalimantan Social Forestry and Environmental Partnership Institute. The obstacles in peat land management is slow developmet of infrastructure, lack of human resource capacity to manage peatlands, lack of coordination between farmers and peat care parties, lack of farmers’understanding of regulation related to peatland management and lack of motivation from farmers to manage the land other than vegetables monoculture. Effective guidance and communication is one form of effective solutions for managing peatlands.